2008
DOI: 10.1097/qco.0b013e3282f54fff
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory infection complicating HIV infection

Abstract: Purpose of review-Respiratory infections remain a major cause of morbidity among HIVinfected persons. Thus, an up-to-date knowledge of recent advances regarding HIV-associated opportunistic pneumonias is crucial to the optimal care of persons with HIV.Recent findings-Bacterial pneumonia is the most common HIV-associated opportunistic pneumonia in the United States and its incidence remains appreciable. Worldwide, tuberculosis (TB) dominates the clinical picture. The absence of rapid, affordable diagnostics for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…After PCP prophylaxis, the incidence of Pneumocystis infection greatly decreased in the USA and Europe. Additionally, some studies have suggested that prophylaxis with trimethoprim-sulfamethoxazole (TMP-SMX) could have decreased the incidence of bacterial infections in HIV patients with ,200 CD4 lymphocytes per mm 3 ; however, not all studies agree with this statement [29,30]. Following the introduction of HAART, the relative incidence of aetiologies of HIV-associated pulmonary infections has changed, with bacterial pneumonia replacing PCP as the most frequently encountered cause of these infections [30,31].…”
Section: Epidemiology Of Pulmonary Infections In Hiv-infected Patientsmentioning
confidence: 87%
“…After PCP prophylaxis, the incidence of Pneumocystis infection greatly decreased in the USA and Europe. Additionally, some studies have suggested that prophylaxis with trimethoprim-sulfamethoxazole (TMP-SMX) could have decreased the incidence of bacterial infections in HIV patients with ,200 CD4 lymphocytes per mm 3 ; however, not all studies agree with this statement [29,30]. Following the introduction of HAART, the relative incidence of aetiologies of HIV-associated pulmonary infections has changed, with bacterial pneumonia replacing PCP as the most frequently encountered cause of these infections [30,31].…”
Section: Epidemiology Of Pulmonary Infections In Hiv-infected Patientsmentioning
confidence: 87%
“…11 Interestingly, while low CD4 count ( 200 cells/mm 3 ), no or intermittent use of HAART, smoking, intravenous drug use, and chronic hepatitis have been associated with the development of invasive pneumococcal disease, these factors are not reported to be associated with nasopharyngeal carriage. [24][25][26][27][28][29] One logical explanation is that although these are not risk factors for carriage, once colonized, those with low CD4 count or inconsistent use of HAART are more likely to develop IPD secondary to immune dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating incidental findings detected on coronary computed tomography (CT) imaging (CAC and angiography) in the general population have been published, but did not specifically evaluate HIV-infected subjects [418]. HIV-infected persons may be at higher risk for infectious and malignant conditions [19, 20], which may have implications for the type and number of incidental findings on imaging studies. Incidental findings are important as they not only impact the clinical usefulness, but also the cost-effectiveness, of screening CT scans.…”
Section: Introductionmentioning
confidence: 99%